A Fluorescent Window Into Protein Folding and Aggregation in Cells - Ignatova, Zoya (2008)
Evolutionary selective pressures have tuned the efficiency of the protein-folding reaction in the crowded complex environment in the cell. Nevertheless, the fidelity of folding is imperfect, leading to off-pathway intermolecular interactions that compete with proper folding and to consequent formation of thermodynamically stable aggregates. Such aggregates constitute the histopathological hallmarks of many neurodegenerative pathologies. Yet, most of the approaches to characterize protein folding and/or misfolding are limited to in vitro conditions. Here, we describe a strategy to directly monitor the behavior of a protein in prokaryotic and eukaryotic cells. The method is based on incorporation of structurally non-perturbing, specific binding motifs for a bis-arsenical fluoroscein dye, FlAsH, in sites that result in distinct dye fluorescence signals for the folded and unfolded states of the protein under study. Our approach has been developed using as a case study the predominantly β-sheet intracellular lipid-binding protein, cellular retinoic acid-binding protein, alone or as a chimera fused to the exon 1-encoded fragment of huntingtin, which harbors a polyglutamine repeat tract. We have designed protocols to label this protein in vivo and to monitor the resulting fluorescence signal, which reports on any misfolding transition and formation of aggregates, yielding quantitatively interpretable data.